Internalisasi Wacana Pemberadaban Kolonial Hindia-Belanda dan Kebangkitan Ajaran Tasawuf di Jawa Abad 19: Sebuah Studi Kasus pada Dongeng Jaka Sakbar - Pratama, Muhamad Fahrizal Leo (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2023)
The development of Sufism studies in Java has been carried out by the palace poets in Surakarta in the 19th century. Various works resulting from the Islamization of classical Javanese literature indicate the efforts to transition from Hindu-Buddhist tradition. Along with the Islamization process in Java, in the early 19th to 20th century, Western Orientalists came with a mission to civilize the natives through the Gospel. This article discusses the teachings of Sufism in a Javanese fairy tale entitled Jaka Sakbar and its correlation to the evangelization process in Java in the 19th century. The Jaka Sakbar fairy tale is one of the story fragments in the collection of fairy tales in the Kěmpalan Dongeng Manuscript Collection of the Widyapustaka Library, Pura Pakualaman, Yogyakarta. Fairy tales are often characterized as mere fictional stories that serve only as entertainment. However, fairy tales do not rule out the possibility of becoming a means of social and religious teaching by adding elements of knowledge in a story. In addition, Sufism teachings were quite popular in Java in the 19th century, along with the growth of tarekat in the Nusantara, especially the reconciliation between Sunni Sufism and philosophical Sufism. The intention to include Sufism teachings in manuscripts in Java is a symbolic resistance by the Islamic Mataram Kingdom and Javanese poets due to colonial domination (missionaries) in the 19th century. === Perkembangan studi tasawuf di Jawa, setidaknya telah dilakukan oleh para pujangga Istana di Surakarta pada abad ke-18 hingga 19. Berbagai macam karya hasil Islamisasi terhadap karya Sastra Jawa periode klasik menujukkan terjadinya upaya peralihan dari tradisi Hindu-Budha. Bersamaan dengan proses Islamisasi di Jawa, pada rentang awal abad ke 19 hingga 20an, para Orientalis Barat datang dengan misi pemberadaban melalui kitab injil kepada kaum bumiputera. Artikel ini membahas mengenai ajaran tasawuf dalam sebuah Dongeng Jawa berjudul Jaka Sakbar dan korelasinya terhadap proses internalisasi wacana pemberadaban di Jawa pada abad ke-19. Dongeng Jaka Sakbar merupakan salah satu fragmen cerita dari kumpulan dongeng dalam Naskah Kěmpalan Dongeng Koleksi Perpustakaan Widyapustaka Pura Pakualaman Yogyakarta. Dongeng seringkali dicirikan sebagai sebuah cerita karangan belaka yang berfungsi sebagai hiburan fiktif. Akan tetapi, dongeng tidak menutup kemungkinan menjadi sebuah sarana pengajaran sosial dan agama dengan menambahkan unsur-unsur pengetahuan dalam sebuah cerita. Selain itu, ajaran tasawuf cukup digemari di Jawa pada abad ke-19 bebarengan dengan pertumbuhan tarekat di Nusantara khususnya rekonsiliasi antara tasawuf sunni dan tasawuf falsafi. Adanya intensi untuk memasukkan ajaran tasawuf dalam manuskrip di Jawa, merupakan salah satu bentuk perlawanan simbolik oleh Kerajaan Mataram Islam dan pujangga Jawa akibat dominasi kolonial (misionaris) pada abad ke-19.